Detecting SARS-CoV-2 in the Breath of COVID-19 Patients - Li, Xiaoguang; Li, Jing; Ge, Qinggang; Du, Yuguang; Li, Guoqiang; Li, Wei; Zhang, Tong; Tan, Lei; Zhang, Runqiang; Yuan, Xiaoning; Zhang, He; Zhang, Chen; et al. (Frontiers in Medicine, 2021)
In the COVID-19 outbreaking year 2020, there became a consensus on the fact that the SARS-CoV-2 virus spreads through aerosols. However, it still remains a great challenge to find an efficient detection way of less virus in aerosol, so that the risk of similar infection can be early monitored and then better controlled. Our study aimed to build a swirling aerosol collection (SAC) device to collect viral particles in exhaled breath and subsequently detect SARS-CoV-2 using reverse transcription polymerase chain reaction (RT-PCR). Laboratory tests of the SAC device using aerosolized SARS-CoV-2 pseudovirus, indicate that the SAC device can give a positive result in just 10 seconds with collection distance to the source at 10 cm, when the concentration of the pseudovirus release source at 10,000 copies/mL. The product threshold of the SAC device is estimated 18,000~100,000 s·copies/mL after combining virus concentration and sampling time. Subsequent clinical trials of the device found three positives and 14 negatives out of 27 patients in agreement with pharyngeal swabs, and 10 patients got opposite results; while no positive was found in a healthy control group (n=12). Based on standard curve calibration, several thousands of the virus per minute is revealed in tested exhalations. Furthermore, referring the average tidal volume data of adults, it is estimated that the SARS-CoV-2 virus concentration in exhale about one copy per milliliter is detectable for COVID-19 patients. This validates the original concept of breath detection of SARS-CoV-2 using SAC combined RT-PCR.